2016
DOI: 10.1111/zoj.12427
|View full text |Cite
|
Sign up to set email alerts
|

Palaeobiology of tanaidaceans (Crustacea: Peracarida) from Cretaceous ambers: extending the scarce fossil record of a diverse peracarid group

Abstract: International audienceDiverse assemblages of tanaidacean peracarid crustaceans from western Tethyan continental deposits suggest that the group was relatively common in or around ancient resin-producing forests. Here we report the results of an examination of 13 tanaidacean specimens from three Cretaceous (Albian to Turonian) French amber deposits. Two new species of the fossil family Alavatanaidae are placed in the previously described Early Cretaceous genus Eurotanais: Eurotanais pyrenaensis sp. nov. from Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…However, only one crustacean species (Tanaidacea) has been recorded for Vendean amber Néraudeau et al, 2017). Yet, no parasite-host relationship between epicarideans and tanaidaceans has ever been recorded, and the tanaidaceans known from Vendean amber are too small to represent final hosts of epicarideans (Eurotanais seilacheri in Sánchez-García et al, 2016).…”
Section: Taphonomic Environmentmentioning
confidence: 99%
“…However, only one crustacean species (Tanaidacea) has been recorded for Vendean amber Néraudeau et al, 2017). Yet, no parasite-host relationship between epicarideans and tanaidaceans has ever been recorded, and the tanaidaceans known from Vendean amber are too small to represent final hosts of epicarideans (Eurotanais seilacheri in Sánchez-García et al, 2016).…”
Section: Taphonomic Environmentmentioning
confidence: 99%
“…The remaining Jurassic tanaidacean species have been placed in monotypic (genus-ranked) groups and can simply be referred to by their species names (without generic name) when discussing the possible affinity to the already described species (e.g., Lanham 1965). All other nonmonotypic tanaidacean groups that are only known from fossils are representatives of Tanaidomorpha (vonk & Schram 2007;Sánchez-garcía et al 2015Sánchez-garcía et al , 2016Sánchez-garcía et al , 2017hearD et al 2018).…”
Section: Systematic Challenges Within Tanaidaceamentioning
confidence: 99%
“…1). Fifteen of these species are known from inclusions in amber of the Cretaceous and Neogene (vonk & Schram 2007;Sánchez-garcía et al 2015Sánchez-garcía et al , 2016Sánchez-garcía et al , 2017hearD et al 2018). The remaining fossils come from nonamber sites.…”
Section: Introductionmentioning
confidence: 99%
“…amphipods, Coleman, 2004; testate amoebae, Schmidt et al, 2010; diving beetles, Gómez and Damgaard, 2014). It has been shown that fresh resin flowing into limnetic waters may trap limnetic microorganisms such as algae and testate amoebae and even aquatic arthropods (Schmidt and Dilcher, 2007). Marine microorganisms occur sometimes as contaminants on the surface of, and in fissures reaching into, amber pieces, if the amber-bearing strata were exposed in the tidal zone or if amber was washed ashore after floating in seawater (e.g.…”
Section: Introductionmentioning
confidence: 99%